The use of SQ6R method in increasing EFL students' reading comprehension - Rusmiati, Rusmiati; Maharani, Putri Regina; Susidamaiyanti, Susidamaiyanti (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2022)
This study was carried out to overcome the difficulties in reading comprehension encountered by high school students. The SQ6R method was offered as the appropriate method to solve the problem in this school. It is aimed at assisting students to get reading information and its meaning. This research utilized quantitative method, i.e. experimental research to find the answer as to whether the SQ6R method could increase students' reading comprehension. The sample of this study was 30 students, equally distributed in both experimental group (class IX3) and control group (class IX2), of a junior high school in Central Aceh, Indonesia. The data of the study was gathered by conducting two tests (pre and post with the treatment in between) which was further analyzed by using t-test. The results indicated that although both classes increased their scores in the post-test, the scores of experimental class who experienced the SQ6R method in their learning increased significantly (39 84) and outperformed those in the control class (33 63). Furthermore, the result of t-test was found to be 13.53 which was higher than t-table of 1.4 at a significance level of 0.05. This signified that the hypothesis (Ha) was accepted and the hypothesis (H0) was rejected. Thus, SQ6R method could increase the students reading comprehension. Based on the results, the teachers are recommended to apply this method in their teaching and learning process.